Implementasi Hukum Adat dalam Prosesi Perkawinan Adat Minangkabau - Gumelar Firmansyah; Mina Rabiatul Asiyah; Putri Nadila; Putry Delsa Hasanah (Universitas Kuningan, 2023)
The traditional Minangkabau wedding procession has high social, cultural and religious values. However, in its implementation, Minangkabau traditional marriage processions often face several obstacles, both from a social, cultural and legal perspective. This study aims to find out how the implementation of customary law in the Minangkabau traditional marriage procession, as well as what are the steps of the Minangkabau traditional wedding procession. The results of the study show that the Minangkabau traditional marriage procession is still carried out consistently and follows the applicable customary law. However, there are also obstacles in the application of customary law in Minangkabau traditional marriage processions, such as differences in the interpretation of customary law among the community, lack of support and recognition from the government in carrying out marriage processions, and a lack of understanding of women's rights in marriage processions. which is still limited to the role as an object. This research has been implied to be important in maintaining the continuity of Minangkabau customs and culture in Indonesia, especially in the context of traditional marriages. Therefore, efforts are needed to increase public understanding and awareness regarding customary law and Minangkabau traditional marriage processions, as well as support from the government in carrying out traditional marriage processions in accordance with applicable customary law and recognizing women's rights in traditional marriage processions. Prosesi perkawinan Adat Minangkabau memiliki nilai sosial, budaya, dan agama yang tinggi. Namun dalam pelaksanaannya, prosesi perkawinan adat Minangkabau sering kali menghadapi beberapa kendala, baik dari segi sosial, budaya, maupun hukum. Penelitian ini bertujuan untuk mengetahui bagaimana implementasi hukum adat dalam prosesi perkawinan adat Minangkabau, serta apa saja langkah-langkah prosesi perkawinan adat Minangkabau. Hasil penelitian menunjukkan bahwa prosesi perkawinan adat Minangkabau masih dijalankan secara konsisten dan mengikuti hukum adat yang berlaku. Namun, terdapat juga kendala dalam penerapan hukum adat dalam prosesi perkawinan adat Minangkabau, seperti adanya perbedaan interpretasi hukum adat di antara masyarakat, kurangnya dukungan dan pengakuan dari pihak pemerintah dalam menjalankan prosesi perkawinan, serta kurangnya pemahaman terhadap hak-hak perempuan dalam prosesi perkawinan. yang masih terbatas pada peran sebagai objek. Penelitian ini telah tersirat penting dalam menjaga keberlangsungan adat dan budaya Minangkabau di Indonesia, khususnya dalam konteks perkawinan adat. Oleh karena itu, diperlukan upaya untuk meningkatkan pemahaman dan kesadaran masyarakat terkait dengan hukum adat dan prosesi perkawinan adat Minangkabau, serta dukungan dari pemerintah dalam menjalankan prosesi perkawinan adat yang sesuai dengan hukum adat yang berlaku dan mengakui hak-hak perempuan dalam prosesi perkawinan adat.